Sourcing practices of online news media in Switzerland during the war in Ukraine - Udris, Linards; Vogler, Daniel; Weston, Morley; Eisenegger, Mark (Frontiers in Political Science, 2023)
Introduction In times of war, sourcing becomes a major challenge for journalists. Information is often unavailable because access is restricted or because reporting on the ground is prohibited, too dangerous, or even simply too costly for media having to work with limited resources. Which sources actually shape the news is a highly relevant question because news media still constitute the main channel of information for many citizens, especially when it comes to wars abroad. For a long time, scholars have diagnosed a dominance of official sources in war coverage but have not analyzed whether this is still the case with the advent of social media platforms, which potentially offer journalists other sources. Moreover, the integration of social media sources, such as Twitter or Telegram, is just one of many interdependencies in hybrid media environments. We aim to provide a more holistic understanding of sourcing practices in times of war by analyzing to what extent information from government and military sources, social media, other news media, and news agencies is featured as a main source in reporting on the war in Ukraine. Methods In our paper, we examine how 13 online media in Switzerland cover the war in Ukraine during the first 3 months after Russia's invasion—an example of a period in which journalists must typically identify reliable sources for reporting on the events surrounding such a war. Using a manual content analysis of 1,198 news articles, we analyze the sourcing practices that are visible in the reporting. Results Our results clearly show that information from other news outlets and social media and, above all, from news agencies plays an important role. Structural features of media types lead to distinct sourcing practices. Heavily commercialized, advertising-based media rely on news agency reports, other news media, and social media much more than subscription media or public service media. However, in all media types, actors from the government and the military are the most important source type. Discussion Our study reveals patterns old and new in terms of sourcing practices war coverage in a European country not participating in, but affected by, the major war in Ukraine.